Moving forward : GIS for transportation - Bills, Terry; Mann, Keith (Applyimg GIS, 2021)
Drive innovation, expand capacity, coordinate maintenance, and reduce costs. Location intelligence is changing the way transportation agencies and departments protect and maintain their infrastructure and achieve operational excellence. Mapping plays a big part, but geospatial analytics, real-time dashboards, and mobile applications are driving new, more efficient workflows and paving the way for innovative, cost-effective solutions. With advancements in smart technologies, location intelligence for transportation management is not just for GIS specialists. In Moving Forward: GIS for Transportation, see how ports, airports, transit authorities, and departments of transportation around the world have implemented geographic information systems (GIS) to visualize and analyze data for operational efficiency, safety and security, asset management, and planning and sustainability. In this collection of case studies and guidance, learn about how GIS was used to: * Expand airport capacity within limited space, while saving millions. * Centralize multi-faceted port security for monitoring daily operations. * Coordinate daily transit maintenance work on